Pengembangan Sistem Penarik Mesin Braiding Konvensional dengan Metode Reverse Engineering - Ilham Ali Arridho; Risky Ayu Febriani; Rani Nopriyanti; Heri Setiawan (JURNAL Al-AZHAR INDONESIA SERI SAINS DAN TEKNOLOGI, 2026)
Braiding machines are essential equipment in the textile industry for producing precise fibber or wire interlacements. Most conventional braiding machines in Indonesia are aging and lack adequate technical documentation. As a consequence, maintenance, component replacement, and component reproduction processes become difficult to perform. This study aims to recover technical data and develop the take-up mechanism of a conventional braiding machine through a reverse engineering approach. The research methodology consists of component identification through disassembly, dimensional measurement, 3D CAD modelling, component design modification, preparation of technical drawings, followed by assembly and functional testing. The results show that the modified component design has a simpler geometry, resulting in more efficient assembly and maintenance processes. Functional testing demonstrates that all components operate in accordance with the original mechanism, while performance testing indicates that the take-up system is capable of maintaining constant yarn tension and producing uniform braiding within a speed range of 100–160 RPM. Statistical analysis using an X̄ control chart confirms that the braiding quality remains within statistical control limits without significant deviations. Therefore, this study concludes that the reverse engineering method is effective in providing comprehensive technical documentation, extending machine service life, and supporting local manufacturing independence.Keywords - Dokumentasi Teknis, Mesin Braiding, Reverse Engineering, Sistem Penarik, X-Chart.